2013
DOI: 10.7575/aiac.alls.v.4n.2p.65
|View full text |Cite
|
Sign up to set email alerts
|

Reticent Students in the ESL Classrooms

Abstract: Reticence has always been regarded as a problematic phenomenon among students in the ESL classrooms. Many instructors have expressed their frustrations to decode the reticent behaviour and work out suitable strategies to help students with such behaviour. Whenever such students do not engage in the classroom discourse, they are usually regarded as not having the desire to learn or lacking in cooperation. These explanations seem simplistic, bias and stereotypical. Based on a larger project on students' reticent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 23 publications
1
4
0
3
Order By: Relevance
“…Specifically, the students' low language proficiency which was reported by (21%) of the participants and confirmed by a number of the participants in the interviews (3 out of 10). This finding is consistent with (Tusi, 1996;Hamouda, 2012;Liu, 2005a;Liu, 2005b;Liu & Jackson, 2009) but contradicting to (Wen, clement 2003;Savasci, 2014;Soo and Goh, 2013) who found that students' proficiency in English was not a determining factor of their unwillingness to communicate in the classroom. In this study, the low proficiency in English was the second main cause for students' unwillingness to communicate in the questionnaire.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Specifically, the students' low language proficiency which was reported by (21%) of the participants and confirmed by a number of the participants in the interviews (3 out of 10). This finding is consistent with (Tusi, 1996;Hamouda, 2012;Liu, 2005a;Liu, 2005b;Liu & Jackson, 2009) but contradicting to (Wen, clement 2003;Savasci, 2014;Soo and Goh, 2013) who found that students' proficiency in English was not a determining factor of their unwillingness to communicate in the classroom. In this study, the low proficiency in English was the second main cause for students' unwillingness to communicate in the questionnaire.…”
Section: Discussionsupporting
confidence: 71%
“…The role of language proficiency has been debatable as to whether it causes unwillingness to communicate among EFL students. Some researchers found that low English proficiency caused some students to be reluctant to speak (Tusi, 1996Liu, 2005aLiu, 2005b;Liu & Jackson, 2009) while others found that it was not a determinant factor (Wen, clement 2003;Savasci, 2014;Soo and Goh, 2013). Instead, they found that the proficiency level of students is not a significant factor that hinders them from communicating as such a problem existed among EFL learners from beginner to more advanced levels.…”
Section: Language Proficiencymentioning
confidence: 99%
“…Ferdous (2012) discovered that English & Literature students had a moderate level of language anxiety, especially when they are not prepared. Soo and Goh (2013) argued that the presence of fear for being negatively evaluated could be due to the nature of Asian cultures as most Asian cultures prioritise their "face" and do not wish to be in any situation which could threaten their face. Asian students believed they would "lose their face" when their peers and language teacher know how much knowledge of second language they have; therefore, they tend to be more passive in the teaching-learning process (Rafek, Hani, Ramli, & Hasni, 2015).…”
Section: Fear Of Negative Evaluationmentioning
confidence: 99%
“…Para cualquier docente que conozca el contexto educativo de los países de Asia Oriental, no es nada nuevo decir que el desarrollo de la competencia comunicativa en una lengua extranjera se encuentra con el escollo fundamental de la resistencia a hablar en clase. La renuencia a hablar, entendida como un fenómeno ampliamente constatado por profesores e investigadores (Bao, 2014;Gushendra y Aprianti, 2019;Hsieh, 2015Hsieh, , 2016Jackson, 2002Jackson, , 2003Liu, 2005Liu, , 2006Liu y Jackson, 2009;Liu y Littlewood, 1997;Mendoza, 2016Mendoza, , 2017Riasati, 2014;Shea, 2017;Shimizu, 2006;Soo y Goh, 2013;Talley y Tu, 2015;Tsui, 1996), es extremadamente compleja, ya que en ella actúan factores no solo muy diversos sino estrechamente relacionados entre sí. Hablamos, pues, de un fenómeno multidimensional que dificulta enormemente la práctica y adquisición de la expresión oral dentro de la enseñanza-aprendizaje de lenguas extranjeras.…”
Section: In Troducciónunclassified
“…Entre ellas encontramos todas aquellas relacionadas con el trasfondo cultural confuciano y con el modelo de sociedad colectivista: el respeto hacia la figura del profesor, la modestia, el mantenimiento de la armonía, la importancia del silencio frente al lenguaje, el miedo a hacer el ridículo,... (Bao, 2014;Chang, 2011;He, 2008;Hsieh, 2015;Jackson, 2002Jackson, , 2003Li y Liu, 2011;Liu, 2005;Shimizu, 2006). Por otro lado, se alude a factores personales o psicológicos: ansiedad, timidez, miedo a cometer errores, falta de confianza,… (Tsui, 1996;Gushendra y Aprianti, 2019;Hsieh, 2015;Jackson, 2002Jackson, , 2003Liu, 2005;Liu y Littlewood, 1997;Soo y Goh, 2013). Entre otras razones, algunos trabajos señalan la falta de costumbre a hablar en los modelos pedagógicos tradicionales centrados en la figura del profesor (Bao, 2014;Liu y Littlewood, 1997;Liu, 2005) I S S N : 1 9 8 8 -8430 y otros destacan la baja competencia en la lengua meta (Bao, 2014;Cheng, 2000;Gushendra y Aprianti, 2019;Liu, 2005;Liu y Jackson, 2009;Liu y Littlewood, 1997;Shimizu, 2006;Soo y Goh, 2013).…”
Section: Marco Teóricounclassified